Protective Effect of Modified Suanmei-Tang on Metabolic-Associated Fatty Liver Disease: An Integrated Strategy of Network Pharmacology, Metabolomics, and Transcriptomics - Wang C; Zhao M; Yue Y; Hu C; Zhou C; Zhang Z; He Y; Luo Y; Shen T; Dang S; Yang Y; Zhang Y (Dove Medical Press, 2024)
Chao Wang,1,* Mei Zhao,2,* Yuanyuan Yue,3 Chao Hu,2 Chunqiu Zhou,2 Zhongyi Zhang,2 Yunliang He,4 Yaqi Luo,4 Tao Shen,2 Sijie Dang,4 Yang Yang,4 Yong Zhang2,4 1Traditional Chinese Medicine Department, Qitai Hospital of the Sixth Division, Xinjiang, 831899, People's Republic of China; 2College of Basic Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, 611137, People's Republic of China; 3Department of Ultrasound, Chengdu First People's Hospital, Chengdu, 610095, People's Republic of China; 4Institute of Traditional Chinese Medicine, Sichuan Academy of Chinese Medicine Sciences, Chengdu, 610014, People's Republic of China*These authors contributed equally to this workCorrespondence: Yong Zhang; Yang Yang, Institute of Traditional Chinese Medicine, Sichuan Academy of Chinese Medicine Sciences, Chengdu, People's Republic of China, Email 18692213920@163.com; 18721326@qq.comBackground: Modified Suanmei-Tang (MST) comprises four plants common to both traditional Chinese medicine and culinary applications, and it can potentially alleviate metabolic-associated fatty liver disease (MAFLD) triggered by a high-fat diet (HFD).Purpose: This research aims to investigate the impact and underlying mechanisms of MST in ameliorating MAFLD caused by an HFD.Methods: UHPLC-Q-Orbitrap-MS/MS was used to determine the constituents of MST and to evaluate its effects on MAFLD mouse models. Transcriptomics, network pharmacology, and bioinformatics analysis (including Kyoto Encyclopedia of Genes and Genomes and Gene Set Enrichment Analysis) were utilized to further clarify the mechanisms by which MST acts on MAFLD. The experimental methods included ELISA, real time quantitative PCR (RT-qPCR), Western blot, immunohistochemistry, molecular docking, and metabolomics. Transcriptomics was integrated with metabolomics to find correlations between differentially expressed genes and metabolites, and crucial genes were validated through RT-qPCR.Results: A total of 23 components of MST were identified. The formulation was found to alleviate metabolic disorders, obesity, insulin resistance, inflammation, and oxidative stress in mice with MAFLD. The findings indicate that MST promoted autophagy by suppressing phosphorylation in the PI3K/AKT/mTOR pathway and enhancing lipid management in the livers of MAFLD mice.Conclusion: MST could effectively improve lipid metabolism disorders and liver lipid deposition in MAFLD mice, and its mechanism might be related to regulating the PI3K/AKT/mTOR pathway to improve autophagy. Keywords: modified Suanmei-Tang, MAFLD, transcriptomics, network pharmacology, metabolomics